THE ROLE OF CLOUD TECHNOLOGIES IN EDUCATION: EMPOWERING THE FUTURE OF LEARNING - Rajabova , Gulchexra Salomovna (Innovative Development in Educational Activities, 2023)
Cloud technology has significantly impacted the education sector, transforming the way teaching and learning take place. By leveraging cloud-based tools and platforms, educational institutions, teachers, and students have experienced a wide range of benefits. Cloud technology has enhanced collaboration and connectivity, allowing students and educators to work together seamlessly, irrespective of their physical location. It has also provided accessibility and flexibility, enabling 24/7 access to educational resources and personalized learning experiences. Cloud technology offers cost-effective and scalable solutions for educational institutions, minimizing upfront costs and allowing for resource allocation based on demand. Data security and backup measures provided by the cloud ensure the protection of sensitive information. Additionally, cloud technology’s advanced analytical capabilities enable educators to make data-driven decisions and improve student outcomes.